Top-Beiträge aus unseren Schwesterzeitschriften - A, Steffen; RM W, Ward; MG, Tay; RM, Edkins; F, Seeler; M van, Leeuwen; LO, Pålsson; A, Beeby; AS, Batsanov; JAK, Howard; TB, Marder (Wiley Publications, 2014)
Lighting up focal adhesion organization: With recent advances in super-resolution microscopy, in particular with the emergence of single-molecule localization microscopy (SMLM), it has become possible to probe the spatial and temporal organization of focal adhesions at unprecedented resolution. Here, the applications of SMLM to focal adhesion structure and dynamics, as well as recent improvements in SMLM instrumentation and analysis are discussed.